Advancing intergroup contact theory: Comments on the issue's articles. (4th March 2021) - Pettigrew, Thomas F.
Abstract: Concerns about intergroup contact have a long and somewhat tortuous history. Shaped largely by Social Darwinism dogma, early theorizing anticipated negative effects. Following World War II, however, a more optimistic view took hold, and social psychological research began to study the phenomenon. Allport's (1954) influential book, the Nature of Prejudice, focused social psychological attention on intergroup contact and shaped research on it for the rest of the 20th century. Now the domain has developed into a complex and intricate theory, complete with multiple forms of contact and numerous moderating and mediating variables—as demonstrated in the articles throughout this JSI issue. Within this historical context of the theory's development, this article then comments on each of the previous articles and their further advances to the theory.